A search for H-chondritic chromite grains in sediments that formed immediately after the breakup of the L-chondrite parent body 470 Ma ago. (15th March 2016) - Heck, Philipp R.; Schmitz, Birger; Rout, Surya S.; Tenner, Travis; Villalon, Krysten; Cronholm, Anders; Terfelt, Fredrik; Kita, Noriko T.
Abstract: A large abundance of L-chondritic material, mainly in the form of fossil meteorites and chromite grains from micrometeorites, has been found in mid-Ordovician 470 Ma old sediments globally. The material has been determined to be ejecta from the L chondrite parent body breakup event, a major collision in the asteroid belt 470 Ma ago. In this study we search the same sediments for H-chondritic chromite grains in order to improve our understanding of the extraterrestrial flux to Earth after the asteroid breakup event. We have used SIMS in conjunction with quantitative SEM/EDS to determine the three oxygen isotopic and elemental compositions, respectively, of a total of 120 randomly selected, sediment-dispersed extraterrestrial chromite grains mainly representing micrometeorites from 470 Ma old post-breakup limestone from the Thorsberg quarry in Sweden and the Lynna River site in Russia. We show that 99% or more of the grains are L-chondritic, whereas the H-chondritic fraction is 1% or less. The L-/H-chondrite ratio after the breakup thus was >99 compared to 1.1 in today's meteoritic flux. This represents independent evidence, in agreement with previous estimates based on sediment-dispersed extraterrestrial chromite grain abundances and sedimentation rates, of a two orders of magnitude higher post-breakup flux of L-chondritic material in the micrometeorite fraction. Finally, we confirm the usefulness of three oxygen isotopic SIMS analyses of individual extraterrestrial chromite grains for classification of equilibrated ordinary chondrites. The H- and L-chondritic chromites differ both in their three oxygen isotopic and elemental compositions, but there is some overlap between the groups. In chromite, TiO2 is the oxide most resistant to diagenesis, and the combined application of TiO2 and oxygen three-isotope analysis can resolve uncertainties arising from the compositional overlaps.